Finite element analysis of burr formation and an automatic online micro-deburring method in precise end-face grinding process. (December 2017) - Dong, Dapeng; Song, Jinbang; Yu, Dedong; Chen, Ming
A new approach is presented in this article for modeling and analysis of precise end-face grinding burr formation. The aim of this approach is to develop an automatic online deburring method that utilizes a precision motion control mechanism and effective deburring tools. Servo valve cores widely used in aerospace industry were employed as the workpiece in this study. After precision external grinding process, as a rule, the way of end-face grinding is adopted to get qualified working edges; the precision of these edges are generally required to be micron level or higher. However, after end-face grinding, the outside circle of the working edges will have burrs whose heights range from a few to dozens of microns, and the manual offline burr removal method currently adopted is not only uneasy to control accuracy but also easy for the working edges of the workpiece to lose its integrity and lead to a high rejection rate. In this article, the burr modeling and analysis procedure were used to get the corresponding formation mechanism of burr, and the online precision burr removal equipment was designed reasonably. Therefore, the effective removal of arising micro-burr from end-face grinding and the accuracy of the working edges were very well guaranteed, so as to improve the production efficiency.